Carbon-doped titania flakes with an octahedral bipyramid skeleton structure for the visible-light photocatalytic mineralization of ciprofloxacin. Issue 119 (17th November 2015) - Shi, Jian-Wen; Wang, Zhenyu; He, Chi; Li, Guodong; Niu, Chunming
Abstract : A novel and unique structure, an octahedral bipyramid skeleton, assembled by three pieces of carbon self-doped TiO2 flakes with exposed {001} facets was successfully prepared for the first time. Abstract : Pharmaceutical and Personal Care Products (PPCPs) are emerging contaminants, which can affect water quality and potentially impact drinking water supplies, ecosystems and human health. A novel and unique structure, an octahedral bipyramid skeleton, assembled by three pieces of carbon self-doped TiO2 flakes with exposed {001} facets was explored for the first time to mineralize ciprofloxacin, one of PPCPs. The results demonstrated that the obtained C-doped TiO2 flakes presented higher visible-light photocatalytic activity in comparison with the reported C-doped TiO2 sheets with exposed {001} facets, which can be ascribed to the narrower band gap, the higher percentage of the exposed {001} facts, the larger specific surface area, and the unique octahedral bipyramid skeleton structure.